An eye tracker application in assistive technology - Lim, Guang Liang (Nanyang Technological University, 2023)
Today, some people suffer spinal cord injuries yearly, resulting in paraplegia and quadriplegia. Many of these disabled people cannot care for themselves independently as they are bedridden, resulting in poor quality of life. While assisting devices technology has supported people with disabilities for many years, some devices are wearable and cause difficulty for the user to use. One assisting device technology, such as the eye tracker, a non-wearable device, helps to aid people with disabilities in improving their daily needs. The purpose of this project is to provide an interface for disabled patients to fulfil their daily needs independently, thus reducing the help needed to be provided by caregivers. This project was developed due to the poor quality of life of disabled patients, mainly bedridden patients. The project uses A computer-interfaced-based communicator and home device control system for people with disabilities developed using Eye Tracker. This system detects the eyeball movement and mirrors it on the computer screen. By just looking at the computer monitor, the disabled can:  Express his/her daily needs (e.g., food and drink) easily with caregivers.  Have an active social life. The patient can surf the internet and communicate with others through various social networking platforms, such as Facebook, Twitter, blog, and WhatsApp, as well as through phone messages without the help of caregivers.  Have self-entertainment. The patient can watch videos, listen to online radio, and play computer games.  Wirelessly control home devices such as lights, fans, and doors.  Control motorized wheelchairs. The project is structured into three distinct parts: The first part involves establishing a connection between the eye track devices and the computer to enable communication between devices, the second part involves creating an application for the patients and the last part is the home control devices interface.